COMPARISON OF PREGNANCY OUTCOMES IN SUBCLINICAL HYPOTHYROIDISM WITH EUTHYROIDISM: A PROSPECTIVE COHORT STUDY - R, Priyanka; Sagili, Haritha; Sahoo, Jayaprakash; Devi, Sujithra (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES This study aimed to compare the pregnancy outcome between euthyroid and women with subclinical hypothyroidism (SCH) (TSH: 2.5 – 4 mIU/L) with and without thyroid peroxidase antibodies (TPOAB). METHODOLOGY A total of 178 pregnant females were recruited in the first trimester and those with TSH between 0.1 - 2.4 mIU/L were considered as euthyroid and 2.5 – 4 mIU/L were labelled as SCH. Females with SCH underwent testing for TPOAB. All females were followed until delivery. The maternal complications, mode of delivery and perinatal outcomes were assessed. RESULTS Among those with SCH there was a significantly higher proportion of overweight, obese females (46% vs 69%,p=0.031). The GDM rate was significantly higher (23% vs 16%; p=0.006) in females with SCH when compared to euthyroid females. TPOAB were present in 15 % of women with SCH. Rates of GDM (71% vs 29%; p=0.023), still births (75% vs 25%; p=0.001) were higher and IUGR / SGA (26% vs 72%; p = 0.027), VLBW / LBW (24% vs 81%, p=0.021), need for resuscitation such as suction/oxygen by mask (7% vs 93%, p=0.005) were significantly lower in females with TPOAB versus those without antibodies amongst females with SCH. CONCLUSIONS There appears to be no difference in pregnancy outcomes between females with SCH and euthyroid females except for GDM which was probably due to the presence of higher BMI. Future prospective studies with larger sample size are required to understand better the pregnancy outcomes in SCH in those with and without TPOAB.